QARAQALPAQSTAN RESPUBLIKASÍN EKONOMIKALÍQ RAYONLASTÍRÍWDÍŃ GEOGRAFIYALÍQ TIYKARLARÍ - Uzakbaev, K.K. (SCIENCE and SOCIETY, 2023)
Economic zoning of the Republic of Karakalpakstan is studied geographically in this article. A general description of the branches of specialization of each economic geographical region is given. An economic-geographical map of the Republic of Karakalpakstan has been developed.